2018
DOI: 10.3390/nu10040460
|View full text |Cite
|
Sign up to set email alerts
|

Association between Urinary Aflatoxin (AFM1) and Dietary Intake among Adults in Hulu Langat District, Selangor, Malaysia

Abstract: Aflatoxin is a food contaminant and its exposure through the diet is frequent and ubiquitous. A long-term dietary aflatoxin exposure has been linked to the development of liver cancer in populations with high prevalence of aflatoxin contamination in foods. Therefore, this study was conducted to identify the association between urinary aflatoxin M1 (AFM1), a biomarker of aflatoxin exposure, with the dietary intake among adults in Hulu Langat district, Selangor, Malaysia. Certain food products have higher potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Various studies have reported that high exposure to AF is directly related to the frequent consumption of certain food products such as nuts, nut products, cereals, and spices and herbs [32]. In the present study, children who consumed haricot bean and cow's milk frequently had higher mean urinary AFM1 than those who consumed these foods less frequently.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Various studies have reported that high exposure to AF is directly related to the frequent consumption of certain food products such as nuts, nut products, cereals, and spices and herbs [32]. In the present study, children who consumed haricot bean and cow's milk frequently had higher mean urinary AFM1 than those who consumed these foods less frequently.…”
Section: Discussionsupporting
confidence: 48%
“…In Malaysia, a high amount of AFB1 was detected in nuts and nut products, and among the major contributing factors were the warm and humid weather conditions [43]. Moreover, the improper storage of foods and agricultural products promotes the growth of the fungi, and subsequently the contamination of these products by AF [32,44]. In Indonesia, the tropical climate and inappropriate food safety practices contributed to the AFB1 contamination of maize and nuts [45].…”
Section: Discussionmentioning
confidence: 99%
“…The children's exposure to aflatoxin B 1 was confirmed by analysis of their urine samples for the presence of aflatoxin M 1 . As reported previously, approximately 1.2% to 2.2% of the dietary aflatoxin B 1 intake can be excreted in urine as aflatoxin M 1 [46]. If two minimal intake levels below 10 ng per kg body weight are considered outliers, the average percentage of aflatoxins excreted in the urine as aflatoxin M 1 equals 3.3% ± 2.8%.…”
Section: Discussionmentioning
confidence: 61%
“…Some studies have demonstrated a relationship between urinary aflatoxin levels and dietary exposure. 6 , 17 Although we only quantified acute exposure from urine samples in this study and not diet, it is plausible that the source of exposure may be dietary. Compared to other studies in other regions of Africa with a similar aflatoxin burden, our study showed a similar high burden of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the metabolite AFM1 in urine, is an index of dietary AFB1 exposure. [6][7][8] It has been demonstrated that HCC patients with exposure to this potent carcinogen tend to have 4.5 times more aflatoxins than controls. 3 The interplay of AFB1 with other risk factors for HCC in the setting of HIV in Nigerians is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%